2005
DOI: 10.1016/j.febslet.2004.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SERCA2a is not regulated by calcineurin or upon mechanical unloading in skeletal muscle regeneration

Abstract: This study investigates to what extent the expression of the slow myosin heavy chain (MyHCI) isoform and the slow type sarcoplasmic reticulum Ca 2+ ATPase (SERCA2a) isoform are co-regulated in fibers of regenerating skeletal soleus muscle. Both overexpression of cain, a calcineurin inhibitor, or partial tenotomy prevented the expression of MyHCI but left SERCA2a expression unaffected in fibers of regenerating soleus muscles. These data complement those from different experimental models and clearly show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
5
8
0
Order By: Relevance
“…This suggests that calcineurin has no direct effect on the expression of the calcium sequestering machinery and that the fast-to-slow transformation that occurs in vivo (8) requires other factors, such as thyroid or other circulating hormones. A similar effect has been seen in regenerating soleus muscle where inhibition of calcineurin in isolated fibers prevented the accumulation of type I MHC but had no effect on the expression of the slow sarco(endo)plasmic reticulum Ca 2ϩ ATPase pump (40).…”
Section: Discussionmentioning
confidence: 70%
“…This suggests that calcineurin has no direct effect on the expression of the calcium sequestering machinery and that the fast-to-slow transformation that occurs in vivo (8) requires other factors, such as thyroid or other circulating hormones. A similar effect has been seen in regenerating soleus muscle where inhibition of calcineurin in isolated fibers prevented the accumulation of type I MHC but had no effect on the expression of the slow sarco(endo)plasmic reticulum Ca 2ϩ ATPase pump (40).…”
Section: Discussionmentioning
confidence: 70%
“…An explanation for this disparity may be related to the idea that distinct subsets of MHC-typed fibers are differentially sensitive to neural activation cues mediating the cellular expression of these proteins (13). On the other hand, Zador et al (66,67) showed that overexpression of the calcineurin inhibitor CAIN or partial tenotomy prevented the expression of MHC I in regenerating soleus muscle, whereas slow SERCA2 expression remained elevated. These findings reveal that the regulation of SERCA2 expression is distinct from that of the slow myosin and that it may be modulated by neuronal activity but is not entirely dependent on it.…”
Section: Discussionmentioning
confidence: 93%
“…Muscle necrosis was induced by the in situ injection of notexin, a snake venom (Harris et al 1975;Harris 2003) with modiWcations assuring the complete degradation of each Wber (Zádor et al 1996). The ensuing regeneration process in the soleus muscle was found to be remarkably reproducible as assessed by histological inspection and by a number of biochemical parameters (Zádor et al 1996(Zádor et al , 2001(Zádor et al , 2002(Zádor et al , 2005(Zádor et al , 2007. Transfection with 30 g of SERCA1b RNAi expressing pSuperEGFP vector in 50 l of 20% sucrose on day 4 of regeneration was done, as described previously (Zádor and Wuytack 2003).…”
Section: Methodsmentioning
confidence: 99%
“…3e, f). However, we have previously shown that because of unknown reasons the MyHC1 can be abolished also in Wbers without detectable cain expression in the cain transfected regenerating soleus muscle (Zádor et al 2005). Therefore, in support of the interpretation of the distinct results received using cotransfection or subsequent transfection, we also show that cotransfection of the 1:1 mix of two plasmids (pEGFP and pDsRED) aVected the same Wbers (SI 3a), while the separate transfection of the two plasmids aVected diVerent Wbers (SI 3b).…”
Section: Serca1b-directed Rnai Stimulates Muscle Regenerationmentioning
confidence: 96%